NADPH Oxidase—Dependent Superoxide Production Is Associated With Carotid Intima-Media Thickness in Subjects Free of Clinical Atherosclerotic Disease - Zalba, Guillermo; Beloqui, Oscar; San José, Gorka; Moreno, María U.; Fortuño, Ana; Díez, Javier (Arteriosclerosis, thrombosis, and vascular biology, 2005)
OBJECTIVE—Oxidative stress plays a critical role in the pathogenesis of atherosclerosis. The NADPH oxidase constitutes the main source of superoxide in phagocytic and vascular cells. This study aimed to investigate the levels of NADPH oxidase–mediated superoxide production in phagocytic cells and the association between phagocytic superoxide production and carotid intima-media thickness (IMT), a surrogate marker of asymptomatic atherosclerosis. METHODS AND RESULTS—NADPH oxidase–mediated superoxide production was determined by a chemiluminescence assay using lucigenin and associated with IMT for 184 asymptomatic subjects free of overt clinical atherosclerotic disease. Compared with individuals in the lowest tertile of superoxide production, those in the upper tertile (>20 counts/sec) showed significantly higher IMT (P<0.05). In correlation analysis, a positive relationship was found between superoxide production and carotid IMT. Superoxide production also correlated positively (P<0.05) with body mass index (BMI). In multivariate analysis, the association of superoxide production with carotid IMT remained significant after adjustment for age, sex, systolic blood pressure, BMI, triglycerides, glucose, and smoking. CONCLUSIONS—In a population sample of adults without clinically overt atherosclerotic disease, increased NADPH oxidase activity was associated with enhanced carotid IMT, suggesting a relationship between phagocytic NADPH oxidase–mediated oxidative stress and the development of atherosclerosis.